Diverse Roles of the Salicylic Acid Receptors NPR1 and NPR3/NPR4 in Plant Immunity. Issue 12 (9th October 2020) - Liu, Yanan; Sun, Tongjun; Sun, Yulin; Zhang, Yanjun; Radojičić, Ana; Ding, Yuli; Tian, Hainan; Huang, Xingchuan; Lan, Jiameng; Chen, Siyu; Orduna, Alberto Ruiz; Zhang, Kewei; et al.
Abstract : Perception of SA by its receptors is required for activation of NHP biosynthesis during SAR, plays crucial roles in PTI and ETI, and is involved in regulating SA 5-hydroxylation and glycosylation. Abstract: The plant defense hormone salicylic acid (SA) is perceived by two classes of receptors, NPR1 and NPR3/NPR4. They function in two parallel pathways to regulate SA-induced defense gene expression. To better understand the roles of the SA receptors in plant defense, we systematically analyzed their contributions to different aspects of Arabidopsis ( Arabidopsis thaliana ) plant immunity using the SA-insensitive npr1-1 npr4-4D double mutant. We found that perception of SA by NPR1 and NPR4 is required for activation of N -hydroxypipecolic acid biosynthesis, which is essential for inducing systemic acquired resistance. In addition, both pattern-triggered immunity (PTI) and effector-triggered immunity (ETI) are severely compromised in the npr1-1 npr4-4D double mutant. Interestingly, the PTI and ETI attenuation in npr1-1 npr4-4D is more dramatic compared with the SA-induction deficient2-1 ( sid2-1 ) mutant, suggesting that the perception of residual levels of SA in sid2-1 also contributes to immunity. Furthermore, NPR1 and NPR4 are involved in positive feedback amplification of SA biosynthesis and regulation of SA homeostasis through modifications including 5-hydroxylation and glycosylation. Thus, the SA receptors NPR1 and NPR4 play broad roles in plant immunity.